Experimental Study on Bolt-Spliced Prefabricated Steel Frame Beams - Ran He; Zaihua Zhang; Jingchao Li (Advances in Civil Engineering)
The prefabricated steel structural residence is characterized by modularization and standardization, which meets the requirement of industrial development. The steel frame beam needs to be fabricated in segments and assembled in site due to the limitation of transportation. In practical engineering, the steel frame beams need to be spliced along the beam span. A robust connection between the two steel beam segments is necessary as it will influence the load bearing capacity, stiffness, and stability of the steel frame. In total, 12 specimens were tested to investigate the influence of spliced types, loading patterns, and bolt types on the performance of the steel frame. The observed failure modes, load versus displacement curves, and moment versus rotation angle curves are presented. The test results show that the strength and deformability of bolt-spliced connections are generally good and similar to those of the prototype beam.